Family Social Support and Work Stress on Night Shift Bus Drivers - Putra, Adi Kurniawan (ANIMA Indonesian Psychological Journal, 2011)
The goal of this research was to find the relation between family social support and work stresson night shift bus drivers. Subjects were night shift bus drivers (N = 38) in Temanggung, chosenby using the simple random sampling technique. Data regarding the family social support andwork stress were collected using two surveys, with 31 and 20 items respectively. Correlationanalysis uses the Pearson Product Moment. Result showed a negative significant correlationbetween family social support and work stress in night shift bus drivers, with the r score of -.647 (p < .05). This means that the higher the family social support score, the lower the workstress score will be on night shift bus drivers. The variance of the work stress variable can beexplained by using the family social support variable, scoring at 41.86% (r2 = - .647). Tujuan penelitian ini adalah melihat hubungan dukungan sosial keluarga terhadap stress kerjasopir bus malam. Subjek adalah para sopir bus malam (N = 38) di Temanggung yang diperolehmelalui simple random sampling. Data dukungan sosial keluarga dan data stres kerja diperolehmelalui pengisian angket, masing-masing terdiri atas 31 dan 20 butir. Hasil analisis korelasiyang menggunakan rumus Pearson Product Moment menunjukkan bahwa ada hubungan negatifyang signifikan antara dukungan sosial keluarga dan stres kerja sopir bus malam, dengan (r)sebesar - .647 (p < .05). Hal ini berarti semakin tinggi dukungan sosial keluarga, maka semakinrendah stres kerja pada sopir bus malam dan sebaliknya. Variansi skor variabel stres kerja dapatdijelaskan oleh variabel dukungan sosial keluarga sebesar 41.86% (r2 = - .647).